Analisis Geohidrologi Limpasan Permukaan Menggunakan Sistem Informasi Geografis Bagian Hulu Sub Das Tangka Provinsi Sulawesi Selatan - Rohaya Langkoke; Jamal Rauf Husain; Ilham Alimuddin; Faisal Faisal (Universitas Muslim Indonesia, 2023)
Water is the source of life so that makes water an important component. Geohydrological analysis of surface runoff aims to investigate changes in the geohydrological cycle due to geomorphological processes that turn water into surface runoff from previously seeping below the surface. This research uses the Bransby-William’s method in the analysis of runoff coefficients which consider the parameters of relief, soil infiltration, land cover, surface storage, and rainfall intensity. The research area is located in the upstream part of the Tangka sub-watershed, South Sulawesi Province, specifically at coordinates 5°07’58.9” – 5°17’23.1” South Latitude and 119° 52’ 45.2”- 120° 00’ 20.5” East Longitude. Surface runoff is 48.87%, resulting in a large potential for flooding and landslides. The surface flow discharge is 385,468 m3/second.